Psychological, social and biological alterations in the climacteric woman - Ângela Regina de Vasconcelos Silva; Cristiana Belchior de Araújo; Raimunda Magalhães da Silva (Universidade de Fortaleza, 2003)
During a long time, the understanding and the treatment of the symptoms and upset of the climacteric were attributed to the modifications of physical order with emotional reflexes. This work tried to identify the most frequent psychological, social and biological alterations in the climacteric, seeking to the adaptation and effectiveness of the nursing interventions.It is a study of exploratory and descriptive character that tends, as main focus, to know and to contribute for the solution of the problems of the group of the climacteric women. The collection of data was accomplished through interviews, of the which took part in 36 women in the climacteric and post-climacteric phases that frequented the Center of Health, in Fortaleza-CE, selected in the consultations of nursing during the months of November of 2001 to January of 2002. We verified that 25 of the women said to feel irritability, 23, feel fatigues; 22, anxiety, 19, decrease of the libido; 21, stress, 20, insomnia and, 20, depression. On the other hand, we noticed that 24 women felt several changes related to the companion, indicating the couple's sexual frigidity, abuse and the partner's isolation and decrease of the libido, associated to the discomforts in the sexual act. Besides, we observed in the depositions that only 05 women understood that the climacteric is a phase of cares and treatments, while 24 demonstrated total ignorance on the subject. This in the group to end that there is deficiency of information in the services of health and that, in practice of nursing, prevention measures and attention should be implemented to the climacteric women, with base in their perceptions and experiences, for help them to overcome the difficulties of the situation.